79‐4L: Late‐News Paper: Highly Transparent LCD using New Scattering‐type Liquid Crystal with Field Sequential Color Edge Light. Issue 1 (May 2017) - Okuyama, Kentaro; Nakahara, Tae; Numata, Yudai; Nakamura, Tenfu; Mizuno, Manabu; Sugiyama, Hiroki; Nomura, Shinichiro; Takeuchi, Shunpei; Oue, Yoshihide; Kato, Hirofumi; Ito, Shohei; Hasegawa, Akira; et al.
Abstract : We have developed highly transparent color liquid crystal display (LCD) using newly developed scattering‐type liquid crystal, which shows transparent state when voltage is not applied, with field sequential color (FSC) driving method without employing color filter and polarizer. Furthermore the light is directly introduced to the panel glass substrates from the edge of the substrates (not from back surface). At surface of the substrates, the light takes a total reflection by difference of refractive index between glasses and air. So the light propagates through the substrate. On the other hand, when a voltage as higher than a threshold voltage (Vth) is applied to liquid crystal (LC) layer, the light is scattered towards the viewers. This newly developed display has high transmittance (80%), wide color gamut and fast response time.